Kendala Penerapan Qanun Nomor 11 Tahun 2018 tentang Lembaga Keuangan Syariah pada Koperasi di Aceh melalui pendekatan Analisis Fishbone - Susanti; Musfira; Sufitrayati (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2022)
The purpose of this study is to find still minor restrictions on cooperatives in Aceh in the implementation of Qanun No. 11 of 2018 on Islamic financial institutions. The approach used in this study is a qualitative descriptive approach. The data collection methods used were REA, questionnaires, interviews, literature, and co-op documents that have not yet been converted from the traditional system to the Shariah system, with a total population of 197 co-ops, and samples were drawn according to the Srobin formula. , that is, 100 co-ops. The data analysis used was fishbone analysis. there are five main variables namely co-operative management, co-operative staff, co-operative infrastructure and co-operative facilities. In management variables, the majority of administrative staff are women and education is dominated by bachelor's degrees, while co-operative personnel variables, including understanding of co-operatives, are about employment co-operatives. shown to average less than 50%. Average, no professional staff, average-average, run only by administrators. For variable infrastructure, i.e. asset development, turnover, number of members and co-management tools, it is still below average, i.e. below 50%. In the context of an institution involving a PAD (amendment of articles of association) issued by a notary, the cost is not too high, but still normal, but the co-op feels that the notary public has not yet understood the co-op regarding the use of the application. Most cooperatives do not use the Sharia system because they do not need it. In conclusion, the general human resource problem remains a lack of understanding and poor collaborative performance. A recommendation against this obstacle is to continuously and continuously develop cooperatives so that they can increase their efficiency and capacity. In particular, an understanding of the Shariah system can be conveyed and the development of cooperation efficiency can also be promoted.